Сверстюкова рецепція творчості Шевченка з позицій цілісно-системного підходу - Полежаєва, Тетяна Вікторівна; Polezhaeva, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано книгу Євгена Сверстюка «Шевченко понад часом» (2011) і на цілісно-системній базі виявлено вищий вид реалістичного методу – загальнолюдський реалізм, який пояснює світову цінність творчості Шевченка. Виокремлено чотири різновиди реалізму.The article analyzes the book essay Eugene Sverstiuk “Shevchenko over time” (2011). Attention is drawn to the interaction of artistic, journalistic, scientific, and religious critical approach to the study of the author’s genius Shevchenko. The study is based on analysis of the main features of the historical development of Shevchenko XX−XXI centuries. That over this long period has become quite controversial. The study of previous studies on the works of Shevchenko E. Sverstyuk allowed to see the cause of the controversial poet’s perception of the world: it is receptive aesthetics, aesthetic criticism and subjectivity. With the use of an integrated system of universal principles of natural knowledge of the opportunity to highlight four types of realism in world literature (as the naturalism fragmented realism Enlightenment realism, critical realism, the realism of all mankind). Reception creative personality Shevchenko E. Sverstiuk points to the universal values of the poet, natural, humane views and aspirations and it belongs to the universal, natural, humane realism, that is, the Supreme mind the realistic method.
Sverstiuk’s Reception Creativity Shevchenko: Holistic Systemic Approach
Keywords: Сверстюк; Шевченко; секрети вічності; цілісно-системний метод; види реалізму; загальнолюдський реалізм; Sverstyuk; Shevchenko; the secrets of eternity; holistic systematic method; types realism; universal realism